Genetic variation, association analysis, and expression pattern of SMAD3 gene in Chinese cattle - T. Shi; Y. Xu; M.-J. Yang; Y. Zhou; M. Liu; X.-Y. Lan; C.-Z. Lei; X.-L. Qi; F.-P. Lin; Y.-Y. Bai; H. Chen (Czech Journal of Animal Science, 2016)
SMAD3, a member of SMAD transcription factors, plays a key role in transforming growth factor-beta (TGF-β) signalling pathway and regulation of muscle growth. However, there was no strong evidence of association between SMAD3 polymorphisms and body traits in animals. In this study, single nucleotide polymorphisms (SNPs) in SMAD3 gene were detected in four Chinese cattle breeds (Qinchuan, Jiaxian, Nanyang, and Caoyuan) by using DNA pool sequencing and PCR-RFLP, and their effects on gene expression and growth traits were evaluated in Qinchuan cattle. The results showed that four novel SNPs (NC_007308.5 c.-2017A>G, g.101664C>G, g.105829A>G, and g.114523A>G) in promoter, intron 3, and intron 5 were found in four cattle breeds. NC_007308.5 c.-2017A>G and g.114523A>G were significantly (P < 0.05) associated with SMAD3 gene expression. Furthermore, the four SNPs were strikingly (P < 0.05) associated with rump length, chest girth, and body weight in two-year-old Qinchuan cattle. Our results provided the evidence that SNPs in SMAD3 were associated with cattle traits, which showed the possibility that the four SNPs could be novel molecular markers for beef cattle breeding and genetics.